2011
DOI: 10.1111/j.1469-1795.2011.00458.x
|View full text |Cite
|
Sign up to set email alerts
|

Causes of mortality in North American populations of large and medium-sized mammals

Abstract: The proportion of different causes of death (cause-specific mortality) is an important indicator of local ecology and local selective forces shaping behavioral and morphological adaptations and can easily be compared between species. These mortality causes are best measured by remotely monitoring individuals with radio transmitter tags to detect their eventual demise and conducting postmortem examinations to determine the exact cause of death. Although studies of mortality causes have been conducted for many m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 59 publications
1
68
2
Order By: Relevance
“…Attempts to assess responses of organisms to emerging threats (e.g., invasive species, disease, climate change) often are hampered by lack of historical or baseline abundance data (41). We were fortunate to have available effort-corrected data from 1996-1997 comparable to the data on mammal relative abundances we have collected since the proliferation of pythons, allowing us to document declines in numerous mammal species accurately.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to assess responses of organisms to emerging threats (e.g., invasive species, disease, climate change) often are hampered by lack of historical or baseline abundance data (41). We were fortunate to have available effort-corrected data from 1996-1997 comparable to the data on mammal relative abundances we have collected since the proliferation of pythons, allowing us to document declines in numerous mammal species accurately.…”
Section: Discussionmentioning
confidence: 99%
“…Tracking studies have a long history of identifying factors related to animal survival and are the primary way to identify the time, location, and cause of death. A review of mortality in large and medium-sized North American mammals, including over 2000 animals tracked until their death, highlighted the importance of humans (i.e., hunters and cars), which accounted for 52% of mortalities, compared to 35% that fell prey to natural predators (45). Satellite technology allows us to monitor mortality of long-distance migrants, which has recently been shown to be much higher during migration (46).…”
Section: Consequences Of Movement For Individuals Populations and Ementioning
confidence: 99%
“…Similarly, a positive effect of road density on deer abundance could result from reduced predation by humans (hunting) in areas with higher road densities. In their review of causes of mortality of medium and large-sized mammals of North America, Collins and Kays (2011) found that while the probability of an animal-vehicle collision increases with increasing human footprint in the landscape, the rate of hunting decreases over the same gradient. Even if actual predation pressure is not substantially reduced in landscapes with high road densities, deer may be able to detect the presence of predators (the 'landscape of fear' concept: Hebblewhite and Merrill 2009;Manning et al 2009;Laundré et al 2010).…”
Section: Discussionmentioning
confidence: 99%